Respon Padi Gogo (Oryza sativa L.) terhadap Pemberian Biostimulan dari Ekstrak Rumput Laut Padina minor - Zozy Aneloi Noli; Suwirmen Suwirmen; Izmiarti Izmiarti; Reza Oktavia; Putri Aliyyanti (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Currently, seaweed extracts are widely used as plant biostimulants to increase the efficiency of nutrient use, tolerance of abiotic stress, and improve plant quality. In this study, tested the effect of different Padina minor seaweed extract formulas (liquid extract and powder extract) and the frequency of application of Padina minor seaweed extract (b0 = control; b1 = 1 x application; b2 = 2 x application; and b3 = 3 x application) as a biostimulant to the growth of upland rice. From the results of the study, it was found that there was no significant effect of the application of the two extract formulas and the frequency of application, but the administration of Padina minor extract 3 times during vegetative growth increased all growth parameters, such as: plant height, number of tillers, fresh and dry weight of plants, and chlorophyll content. It was concluded that giving Padina minor extract 3 times could increase the vegetative growth of upland rice effectively.